2018
DOI: 10.1039/c7cp06889a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the interactions between sebum triglycerides and water: a molecular dynamics simulation study

Abstract: In recent years, sebum oil has been found to play a key role in the regulation of the hydration of the outermost layer of the skin, the stratum corneum. Understanding how a major component of the sebum oil, the triglyceride tri-cis-6-hexadecenoin (TG), interacts with water is an important step in gaining insight into the water regulation function of the sebum oil. Here we use molecular dynamics simulations to investigate the structural and interfacial properties of TG in bulk and at the air and water interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 57 publications
(57 reference statements)
6
52
0
Order By: Relevance
“…The SLN would then have the chance to develop into one of the crystalline polymorphs. Experimental and computational studies of bulk triglycerides have shown that the tuning fork and chair conformations are the most common in bulk lipid, which is also reflected in our SLN lipid core . Additional simulation work confirms the preference of lipids to adopt the trident conformation at the lipid/water interface and experimental evidence has shown that lipids at the air/water interface are also in the trident conformation …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The SLN would then have the chance to develop into one of the crystalline polymorphs. Experimental and computational studies of bulk triglycerides have shown that the tuning fork and chair conformations are the most common in bulk lipid, which is also reflected in our SLN lipid core . Additional simulation work confirms the preference of lipids to adopt the trident conformation at the lipid/water interface and experimental evidence has shown that lipids at the air/water interface are also in the trident conformation …”
Section: Discussionsupporting
confidence: 72%
“…The angle criteria used to classify a triglyceride molecule is summarized in the Supporting Information. It is the same as used in a previous study however this work defines the vectors from the central carbon (C18) as opposed to the first oxygen in each chain . Determining the length of each vector also provided with an understanding of lipid extension, as shown in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation displayed how environment factors may affect the dynamic organization of phospholipid molecules. Apart from the interactions between lipid and water (Tascini, Noro, Chen, Seddon, & Bresme, ), there are other investigations concerning lipids, such as lipid aggregating into vesicles and bunches (Marrink & Mark, ; Wassall et al., ) and phase transition in lipid systems (Gai et al., ; Marrink, Risselada, & Mark, ).…”
Section: Simulation As An Aid For Food Researchmentioning
confidence: 99%
“…[ Figure 2 and Table 2 were updated. Chen et al (2018) was corrected to Chen et al (2018a) and Chen et al (2018b) in the reference list after initial online publication.] that define the atoms, residues, and their masses, charges, types, and so on involved in a system under study (Cheng et al, 2018;Couallier, Riaublanc, David, & Rousseau, 2018;Foley, Tessier, & Woods, 2012;Watts, Gregory, Frisbie, & Lovas, 2018).…”
Section: Introductionmentioning
confidence: 99%